Immortalised breast epithelia survive prolonged DNA replication stress and return to cycle from a senescent-like state - Maya-Mendoza, A; Merchut-Maya, J M; Bartkova, J; Bartek, J; Streuli, C H; Jackson, D A (Cell death & disease, 2014)
Mammalian cells have mechanisms to counteract the effects of metabolic and exogenous stresses, many of that would be mutagenic if ignored. Damage arising during DNA replication is a major source of mutagenesis. The extent of damage dictates whether cells undergo transient cell cycle arrest and damage repair, senescence or apoptosis. Existing dogma defines these alternative fates as distinct choices. Here we show that immortalised breast epithelial cells are able to survive prolonged S phase arrest and subsequently re-enter cycle after many days of being in an arrested, senescence-like state. Prolonged cell cycle inhibition in fibroblasts induced DNA damage response and cell death. However, in immortalised breast epithelia, efficient S phase arrest minimised chromosome damage and protected sufficient chromatin-bound replication licensing complexes to allow cell cycle re-entry. We propose that our observation could have implications for the design of drug therapies for breast cancer.
Keywords: nádory prsu; DNA Damage; Female; Cell Line, Tumor; ženské pohlaví; Cell Cycle; mléčné žlázy lidské; lidé; S Phase; stárnutí buněk; replikace DNA; Epithelial Cells; Breast Neoplasms; Mammary Glands, Human; buněčný cyklus; poškození DNA; S fáze; Cell Survival; viabilita buněk; DNA Replication; epitelové buňky; Cellular Senescence; nádorové buněčné linie; Humans